Time-Course Evaluation of Body Mass Index in Japanese Children With Obstructive Sleep Apnea Syndrome After Adenotonsillectomy: A Three-Years Follow-Up Study - Ken Fukuda; Hiroki Yasudo; Naoki Ohta; Hiroko Narumi; Nozomi Abe; Shunsuke Tarumoto; Hiroshi Yamashita; Kiyoshi Ichihara; Shouichi Ohga; Shouichi Ohga; Shunji Hasegawa (Frontiers Media S.A., 2020)
Delayed physical growth is a common complication of pediatric obstructive sleep apnea syndrome (OSAS). Adenotonsillectomy (AT) is the first-line treatment for pediatric OSAS. Only a few studies have performed time-course BMI evaluation in pediatric OSAS patients post-operatively. Thus, we aimed to evaluate the time-course changes in pediatric OSAS patients after AT. Thirty-three children with OSAS who underwent AT were included and divided into two groups on the basis of their BMI z-scores (delayed physical growth group, n = 15; non-delayed physical growth group, n = 18). Clinical records of height and weight were collected before AT and at 6, 12, 24, and 36 months after AT. Changes in the mean BMI z-scores of the two groups were assessed up to 36 months. The mean BMI z-score was significantly increased in the delayed physical growth group at 6 months after AT. In contrast, the increase in mean BMI z-score was not observed in the non-delayed physical growth group. Growth improvement was noted in pediatric OSAS patients with delayed physical growth after AT. Our results suggest that AT is a promising therapy for improving the physical growth of pediatric OSAS patients with such problems.